2005
DOI: 10.1093/gerona/60.11.1425
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Progressive Resistance Training on Body Composition in Frail Older Adults: Results of a Randomized, Controlled Trial

Abstract: Three months of supervised PRT induced improvements in maximal voluntary thigh muscle strength and whole body FFM in frail, community-dwelling elderly women and men. This supervised exercise program may not be sufficient to reduce whole-body or intra-abdominal fat area in this population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
169
0
16

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 237 publications
(195 citation statements)
references
References 33 publications
10
169
0
16
Order By: Relevance
“…Reviewing the literature for exercise-induced LBM changes in subjects 50 years and older (Peterson et al 2011) as assessed by DXA shows that WB-EMS effects were well within the range of conventional exercise effects in elderly cohorts. Even with a focus on high-intensity exercise protocols (>70 % 1RM) (Ades 2001;Binder et al 2005;Marques et al 2011b;Nelson et al 1996), no relevant differences can be noted. A direct comparison of the present WB-EMS results and data of our recent 18-month Senior Fitness and Prevention (SEFIP) trial (Kemmler et al 2010c), which also applied an intense resistance protocol using identical methods and a comparable cohort of community living elderly women (69±4 years) who were however less lean (BMI, 26±4 kg/m 2 ), revealed comparable net effects (WB-EMS vs. CG) for ASMM (WB-EMS, 294 g vs. SEFIP, 299 g) and LBM (WB-EMS, 568 g vs. SEFIP, 509 g).…”
Section: Discussionmentioning
confidence: 98%
“…Reviewing the literature for exercise-induced LBM changes in subjects 50 years and older (Peterson et al 2011) as assessed by DXA shows that WB-EMS effects were well within the range of conventional exercise effects in elderly cohorts. Even with a focus on high-intensity exercise protocols (>70 % 1RM) (Ades 2001;Binder et al 2005;Marques et al 2011b;Nelson et al 1996), no relevant differences can be noted. A direct comparison of the present WB-EMS results and data of our recent 18-month Senior Fitness and Prevention (SEFIP) trial (Kemmler et al 2010c), which also applied an intense resistance protocol using identical methods and a comparable cohort of community living elderly women (69±4 years) who were however less lean (BMI, 26±4 kg/m 2 ), revealed comparable net effects (WB-EMS vs. CG) for ASMM (WB-EMS, 294 g vs. SEFIP, 299 g) and LBM (WB-EMS, 568 g vs. SEFIP, 509 g).…”
Section: Discussionmentioning
confidence: 98%
“…Several randomized clinical trials have demonstrated the positive effects of specific physical activity programs in diseased or frail older adults (Ettinger et al 1997;Chin et al 2008;Daniels et al 2008;Binder et al 2005;Messier et al 2000). For example, in FAST study (Ettinger et al 1997), a randomized trial conducted among 439 community dwelling older adults with knee osteoarthritis, selfreported physical function was significantly improved among those participating in an 18-months aerobic exercise training or resistance exercise training program, as opposed to those participating in a health Exacerbation of underlying joint disease education program.…”
Section: Physical Activity and Functional Impairmentmentioning
confidence: 99%
“…In 2012, Stenholm et al reported that lifestyle (e.g., education, leisure time and work-related physical activity, smoking behavior, alcohol consumption), and physical health (e.g., chronic conditions such as hypertension, coronary heart disease, cardiovascular disease, or diabetes mellitus) earlier in life determine the rate of muscle strength decline (measured as handgrip strength) in old age (Stenholm et al 2012). Furthermore, various studies have evidenced that nutritional supplementation-such as vitamin D or protein intake-and exercise interventions can have a beneficial effect on muscle strength and physical performance, even in older populations (Bonnefoy et al 2003;Binder et al 2005;Chale-Rush et al 2010;Pahor et al 2014;Cesari et al 2015). In 2015, Sahni et al found a significantly higher leg lean mass in both males (n = 1166, age 60.2 ± 9.3 years) and females (n = 1509, age 59.0 ± 9.3 years) in the highest quartile of total protein and animal protein intake compared with those in the lowest quartiles (Sahni et al 2015).…”
Section: Introductionmentioning
confidence: 99%